The Euro-Mediterranean Partnership : Trade in Services as an Alternative to Migration? - Hoekman, Bernard; Ozden, Caglar (2012)
This article discusses options to facilitate movement of workers between high-income and developing countries within the framework of trade agreements, focusing on the European Union's partnership agreements with neighbouring countries. Existing frameworks for co-operation offer the possibility of expanding temporary rather than longer-term or permanent movement of workers since extant trade agreements provide scope for negotiating specific market access commitments for services, including those delivered through the cross-border movement of natural persons. Even though the potential for such 'embodied' trade in services will not be anywhere near what would be associated with substantial liberalization of migration regimes, furthering the services trade dimension in the European Union's trade agreements offers significant potential Pareto gains. For the partner countries these gains from temporary movement of service providers are both direct--through greater employment and revenue from providing services in the European Union--and indirect--by helping to increase and sustain higher growth at home.